Aplikasi Grey Level Coocurent Matrix(Glcm) Menggunakan Matlab Gui Dan Ann Dalam Identifikasi Penyakit Pada Tanaman Porang - Marwan, Fayyadh Ats Tsaqib; Ramadhanti, Hauraisya Nayla; Wahid, Neyla Cahyaningrum; Rimantho, Dedi (Jurnal Teknologi Elekterika, 2023)
Porang is an Indonesian export product, its export potential still has enormous value opportunities. Diseases in porang are caused by several things, including pathogenic bacteria which damage the tubers. Caterpillars and grasshoppers also become diseases in people. The GLCM method provides speed of initial identification of diseases in porang. ANN (Artificial Neural Network) helps classify diseases in porang plants. The Matlab GUI is used as an graphical interface for the porang disease classification application.